Inhibitory effect of sugarcane molasses extract on the formation of Nε-(carboxymethyl)lysine and Nε-(carboxyethyl)lysine. (15th April 2017) - Yu, Pei; Xu, Xian-Bing; Yu, Shu-Juan
Highlights: Sugarcane molasses extract (SME) was used for inhibiting CML and CEL formation. SME exhibits perfect antioxidant activities and carbonyl scavenging capacities. SME could be used as effective food ingredients to reduce dietary AGEs. Abstract: Molasses, the main byproduct of sugar production, is a well-known source of phenolic compounds. In this study, the effect of sugarcane molasses extract on the formation of N ε -(carboxymethyl)lysine (CML) and N ε -(carboxyethyl)lysine (CEL) was investigated in glucose-lysine model reaction systems. Results showed that sugarcane molasses extract significantly and dose dependently inhibited the formation of CML and CEL in model reaction systems. The antiglycation activities of sugarcane molasses extract were not only brought about by its antioxidant activities but also associated with its trapping abilities of reactive carbonyl species, such as glyoxal (GO) and methylglyoxal (MGO), the key intermediate compound for the formation of CML and CEL. Besides, the presence of sugarcane molasses extract effectively reduced the extent of browning. The present study emphasized the potential health effects of sugarcane molasses and the possibility of using byproducts as effective ingredients to reduce dietary Maillard reaction end products.